Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Need someone to show me the solution. and tell me how ! $$(P÷N) × (N×(N+1)÷2) + N×(1-P) = N×(1-(P÷2)) + (P÷2)$$

share|improve this question

2 Answers 2

up vote 1 down vote accepted

$$\begin{align*}\frac{P}{\color{red}{N}}\cdot\frac{\color{red}{N}(N+1)}2+N(1-P)&=\frac{P(N+1)}2+N(1-P)\\ &=\frac{P(N+1)}2+\frac{2N(1-P)}2\\ &=\frac{PN+P+2N-2NP}2\\ &=\frac{P+2N-NP}2\\ &=\frac{P}2+\frac{2N-NP}2\\ &=\frac{P}2+N\left(\frac{2-P}2\right)\\ &=\frac{P}2+N\left(1-\frac{P}2\right) \end{align*}$$

share|improve this answer

\begin{align} \dfrac{P}{N} \times \dfrac{N(N+1)}2 + N\times (1-P) & = \underbrace{P \times \dfrac{N+1}{2} + N \times (1-P)}_{\text{Cancelling out the $N$ from the first term}}\\ & = \underbrace{\dfrac{PN + P}2 + N - NP}_{\text{$P \times (N+1) = PN + P$ and $N \times (1-P) = N - NP$}}\\ & = \underbrace{\dfrac{PN + P +2N - 2NP}2}_{\text{Take the lcm $2$.}}\\ & = \underbrace{\dfrac{P + 2N -NP}2}_{PN - 2NP = -NP}\\ & = \dfrac{P}2 + \dfrac{2N - NP}2\\ & = \underbrace{N\dfrac{2-P}2 + \dfrac{P}2}_{\text{Factor out $N$ from $2N-NP$}}\\ & = \underbrace{N \left(1 - \dfrac{P}2\right) + \dfrac{P}2}_{\text{Making use of the fact that $\dfrac{2-P}2 = \dfrac22 - \dfrac{P}2 = 1 - \dfrac{P}2$}} \end{align}

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.